Immunohistochemical characterization of endometrial leucocytes in endometritis - Disep, B; Innes, B A; Cochrane, H R; Tijani, S; Bulmer, J N (Histopathology, 2004)
Aims:  Leucocytes are a normal and variable component of the endometrial stromal cell population. The aim of this study was to characterize endometrial leucocytes in established cases of endometritis in order to determine whether there are objective characteristics of the leucocyte infiltrate which would allow its identification as part of an inflammatory process rather then the normal physiological leucocyte infiltrate. Methods and results:  We examined endometrial tissue from 79 cases of endometritis and 22 histologically normal controls. Leucocytes were characterized immunohistochemically for CD45, CD20, CD68, CD3 and CD56 and numbers were analysed semiquantitatively on a scale of 0–4. In many endometritis cases the overall number of leucocytes was increased. Furthermore, leucocytes were unusually distributed with a tendency to accumulate superficially beneath the endometrial surface. Whilst numbers of macrophages, T lymphocytes and endometrial granulated lymphocytes (uterine natural killer cells) did not differ between endometritis samples and controls, most endometritis cases contained a substantially increased number of B cells, which normally represent 1% or less of the endometrial leucocyte population. B lymphocytes were also observed in unusual locations such as intraepithelially and within glandular lumina. Conclusions:  These results suggest that immunohistochemical characterization of endometrial leucocytes may be helpful in establishing a diagnosis of endometritis in equivocal cases.